MEMPREDIKSI HUBUNGAN LOYALITAS MEREK, RASA KEIKUTSERTAAN, KECOCOKAN CITRA DIRI DAN KONSUMSI TERAKHIR TERHADAP KESEJAHTERAAN KONSUMEN : STUDI EMPIRIS PADA KEDAI KOPI STARBUCKS - Hendro .; Sabrina O. Sihombing (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2011)
Modern lifesytle affects the increasing food and beverage industry. People spend their time at cafe, restaurant, or coffee shop to interact with other people. Consumers are faced with many choices of cafe, restaurant, and coffee shop nowadays. However, people may choose one specific cafe, restaurant, or coffee shop based on perception toward well-being. In otherwords, consumer well-being (CWB) refers to the extent to which a particular consumer good or service creates an overall perception of the quality-of-life impact of that product. This research applied a model which was developed by Sirgy and Grzeskowiak (2007) to predict consumer well- being. The model was tested among 265 respondents. Structural equation modeling was applied to analyze the data. The results indicated that CWB was significantly predicted brandcommunity belongingness, and the effect of brand loyalty on CWB was moderated by selfimage congruence.Keywords: consumer well-being, consumer satisfaction, self-image, brand-community belongingness